2013
DOI: 10.1530/eje-12-0531
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical cord levels of sclerostin, placental weight, and birth weight are predictors of total bone mineral content in neonates

Abstract: Context: During pregnancy, changes occur in the maternal calcium homeostasis to fulfill fetal demand. We hypothesized that the fibroblast growth factor 23 (FGF23) system and Wnt signaling pathway are important for normal skeletal development in the offspring. Aims: Circulating a-klotho, FGF23, sclerostin, and 25-hydroxyvitamin D (25(OH)D) at the fetal and maternal sides of the placenta were measured to investigate associations with newborn bone mass independent of maternal BMI, calcium and phosphate levels, pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 42 publications
4
11
0
Order By: Relevance
“…The relationship between maternal vitamin D and foetal bone development has recently been reviewed (31), but no association between maternal vitamin D levels and neonatal bone mineral content was demonstrated. This observation is in agreement with our recent findings, where we found that neither foetal nor maternal 25(OH)D seemed to have a major role in bone mass development in the neonates (32).…”
Section: Introductionsupporting
confidence: 94%
See 2 more Smart Citations
“…The relationship between maternal vitamin D and foetal bone development has recently been reviewed (31), but no association between maternal vitamin D levels and neonatal bone mineral content was demonstrated. This observation is in agreement with our recent findings, where we found that neither foetal nor maternal 25(OH)D seemed to have a major role in bone mass development in the neonates (32).…”
Section: Introductionsupporting
confidence: 94%
“…The study sample was based on a sub-cohort of 202 women from the STORK study: an observational, prospective study of determinants of foetal growth and birth weight in healthy pregnancies for which the details have been published previously (32,33). In short, the STORK cohort consists of women of Scandinavian heritage (nZ1031), who registered for obstetric care at Oslo University Hospital Rikshospitalet, from 2001 to 2008.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the levels of FGF23 were similar in the maternal and the fetal compartment, those of a-klotho were higher in the umbilical cord plasma. However, neither FGF23 nor a-klotho was associated with fetal BMC (49).…”
Section: Other Regulatorsmentioning
confidence: 81%
“…A recent Scandinavian study (49) has found that the circulating levels of sclerostin were lower in the mother at the 30-32 weeks of pregnancy than in the umbilical cord at delivery. Interestingly, cord sclerostin, but not maternal sclerostin, was significantly associated with dual-energy X-ray absorptiometry (DXA)-measured total body bone mineral content (BMC) in the newborn.…”
Section: Other Regulatorsmentioning
confidence: 93%